Conceptual analysis of mental health according to Muslim scholars for Stress Prevention Project (STOP) in Gombak - Ahmad, Nadzrah; Wan Yusoff, Wan Mazwati; Janon, Nazariah Shar'ie; Lukie, Inkan; Baharin, Auni (2019)
This paper attempts to highlight the process of analysing the concepts used by the Muslims scholars to identify stress and its causes and implications. Clarification and identification of these concepts may assist the psychologists involved in the Stress Prevention Project (STOP) to enrich their interview protocol preparatory procedures with Islamic point of view. Islamic perspective of stress will significantly assist to understand further the underlying symptoms and causes of lack mental hygiene among youth in Gombak who are Muslims in majority. This research employs qualitative method of philosophical analysis involving breaking down concepts into fundamental elements in order to comprehend further certain phenomenon or issue. This further known as conceptual analysis. Outcome of the study suggests that Muslim scholars were highly of the view that spiritual condition of a person determines his/her mental state. Scholars were also of the view that mental health could be the result of past and future encounters which may invoke disturbances and instability in one’s mind. Terms such as ghummah, qalaq and ḥuzn were among the few utilized by Muslim scholars to indicate mental state to denote low mental hygiene.